2017
DOI: 10.1002/hbm.23802
|View full text |Cite
|
Sign up to set email alerts
|

Preferential encoding of movement amplitude and speed in the primary motor cortex and cerebellum

Abstract: Voluntary movements require control of multiple kinematic parameters, a task carried out by a distributed brain architecture. However, it remains unclear whether regions along the motor system encode single, or rather a mixture of, kinematic parameters during action execution. Here, rapid event-related functional magnetic resonance imaging was used to differentiate brain activity along the motor system during the encoding of movement amplitude, duration, and speed. We present cumulative evidence supporting pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…This has been demonstrated for the posterior putamen, [69][70][71][72] SMA, 70,73 M1, 72,[74][75][76][77] and the cerebellum. 71,72,[77][78][79] Furthermore, it should be noted that this meta-analysis was conducted in studies using a variety of motor tasks implying that any detected difference should not be specific to a certain kind of movement, but rather a general process underlying motor execution. We speculate that the process that is probed in many of these neuroimaging studies in PD might be the modulation of movement vigor, which is a crucial aspect of motor control, 80 and reduced movement vigor constitutes a core motor impairment in PD (clinically termed bradykinesia).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This has been demonstrated for the posterior putamen, [69][70][71][72] SMA, 70,73 M1, 72,[74][75][76][77] and the cerebellum. 71,72,[77][78][79] Furthermore, it should be noted that this meta-analysis was conducted in studies using a variety of motor tasks implying that any detected difference should not be specific to a certain kind of movement, but rather a general process underlying motor execution. We speculate that the process that is probed in many of these neuroimaging studies in PD might be the modulation of movement vigor, which is a crucial aspect of motor control, 80 and reduced movement vigor constitutes a core motor impairment in PD (clinically termed bradykinesia).…”
Section: Discussionmentioning
confidence: 69%
“…Although reverse inference should be taken with caution, 68 there is strong evidence from neuroimaging and electrophysiological studies for a critical role of this network in the modulation of movement vigor. This has been demonstrated for the posterior putamen, 69‐72 SMA, 70,73 M1, 72,74‐77 and the cerebellum 71,72,77‐79 . Furthermore, it should be noted that this meta‐analysis was conducted in studies using a variety of motor tasks implying that any detected difference should not be specific to a certain kind of movement, but rather a general process underlying motor execution.…”
Section: Discussionmentioning
confidence: 72%
“…Voluntary muscle contraction requires distributed activity among several brain structures to encode movement related parameters. For example, neurons within the sensorimotor cortex regulate movement amplitude 40 and direction 41 . Cramer et al 42 demonstrated that neuronal activity within the motor cortex and surrounding regions exhibit a proportional response to force output in healthy adults (more force output equated with more neural activity).…”
Section: Discussionmentioning
confidence: 99%